Molecular mobility, crystallization and melt-memory investigation of molar mass effects on linear and hydroxyl-terminated Poly(ε-caprolactone). (1st March 2022) - Klonos, Panagiotis A.; Bikiaris, Nikolaos D.; Christodoulou, Evi; Zamboulis, Alexandra; Papageorgiou, George Z.; Kyritsis, Apostolos
Abstract: In this work, we synthesized and investigated five linear and –OH terminated poly( ε -caprolactone)s, PCL, prepared by ring opening polymerization. The samples cover the molar mass, M n, range from ∼4 to ∼70 kg/mol. These biobased polyesters are studied combining a sum of experimental techniques for the structure (infra-red spectroscopy, X-ray diffraction), thermal transitions (calorimetry), semicrystalline morphology (polarized microscopy) and molecular dynamics (broadband dielectric spectroscopy). In particular, upon subjecting the samples to carefully selected thermal conditions, involving extreme cases of crystal memory, namely preserved against erased memory, interesting effects were revealed. The role of M n in PCL is initially reflected on the crystallization and, indirectly, on molecular mobility via crystallinity. For the lower M n s, the formation of interchain interactions, in particular, between the backbone carbonyls (–CO) and the chain end groups (–OH) seems to dominate, exhibiting larger temperature widths of self-nucleation (SN). On the other hand, for larger M n s the increased chain-chain entanglements (physical crosslinks) govern, resulting in favored nucleation, however suppressed SN width. The preservation of melt memory is documented by various physical processes to arise from increased fraction of bound carbonyls and result to altered crystals structuring. Then, next to presenting the effect of M n and crystalline fraction on both the static and the dynamic glass transition, we assess in depth the molecular origins of local dynamics. We demonstrate that the expected interchain associations could be directly correlated with changes on the dielectric strength of local γ relaxation, being luckily strong in PCL, due to the involvement of the carbonyl groups, rather than on segmental dynamics ( α relaxation). The latter was affected only in terms of strength and fragility, by the tight or loose semicrystalline morphology, within which the crystals may act both as factors that impose constraints to chains diffusion (low M n ) as well as spatial confinement (higher M n ). Overall, our findings demonstrate the ability to tune the final PCL properties related to crystallization (permeability, mechanical performance), which is desired envisaging future applications (e.g., biomedical, packaging). Graphical abstract: Image 1 Highlights: Linear –OH terminated PCL prepared by Ring Opening Polymerization and investigated. For high molar mass ( M n ) the chain entanglements govern nucleation, however, do not favor melt memory. For low lower M n, the chain-chain interactions, between backbone –CO and end –OH, govern melt-memory. Evaluation of inter-chain interactions and self-nucleation by various and in principle different techniques. Denser upon preservation of melt memory and spatial nano-confinement (for high  M n ).